Abscopal Effects in Metastatic Cancer: Is a Predictive Approach Possible to Improve Individual Outcomes? - Barbara Link (MDPI AG, 2021)
Patients with metastatic cancers often require radiotherapy (RT) as a palliative therapy for cancer pain. RT can, however, also induce systemic antitumor effects outside of the irradiated field (abscopal effects) in various cancer entities. The occurrence of the abscopal effect is associated with a specific immunological activation in response to RT-induced cell death, which is mainly seen under concomitant immune checkpoint blockade. Even if the number of reported apscopal effects has increased since the introduction of immune checkpoint inhibition, its occurrence is still considered rare and unpredictable. The cases reported so far may nevertheless allow for identifying first biomarkers and clinical patterns. We here review biomarkers that may be helpful to predict the occurrence of abscopal effects and hence to optimize therapy for patients with metastatic cancers.